Pro-Fibrogenic and Anti-Inflammatory Potential of a Polyphenol-Enriched Fraction from Annona crassiflora in Skin Repair - de Moura, Francyelle Borges Rosa; Justino, Allisson Benatti; Ferreira, Bruno Antonio; Espindola, Foued Salmen; Araújo, Fernanda de Assis; Tomiosso, Tatiana Carla (Planta Medica, 2019)
A polyphenol-enriched fraction from Annona crassiflora fruit peel (PEF-Ac) containing chlorogenic acid, epi-catechin, procyanidins B2 and C1, quercetin-glucoside, kaempferol, and caffeoyl-glucoside was investigated for its anti-inflammatory, pro-angiogenic, and profibrogenic potential in the healing of cutaneous wounds. Four wounds were performed on the back of C57 mice and the lesions were treated with the vehicle (Vaseline and lanolin) and PEF-Ac at concentrations of 2%, 4%, and 6% for 4 and 7 d. Neutrophils and macrophages activities were evaluated indirectly by the activity of myeloperoxidase and N-acetyl-β-D-glycosaminidase, angiogenesis was evaluated by hemoglobin dosing and vessel count in histological sections, and collagen deposition was assessed from histological sections stained with picrosirius red. PEF-Ac demonstrated anti-inflammatory activity, with reduced activities of neutrophil and macrophage in the cutaneous wounds. In addition, there was an increase in the synthesis of types I and III collagen, as well as in the percentage of wound closure, mainly after 4 d of treatment. On the other hand, PEF-Ac did not present an effective pro-angiogenic activity. A. crassiflora fruit peel showed anti-inflammatory and profibrogenic properties, indicating a promising natural source of bioactive molecules for treatment of cutaneous wounds.
Keywords: Annona crassiflora; Annonaceae; inflammation; wound healing; collagen; polyphenols